Alcohol toolkit: empowering Sabah indigenous communities to reduce alcohol-related harm - Helen Benedict Lasimbang; Eckermann, Liz; Shoesmith, Wendy Diana; James, Sandi; Aisat Ellik Igau @ Oswald Iggau; Lee, Kuok Tiung; Jephte Sompud; Asong Joseph (Penerbit UMS, 2019)
Alcohol misuse compromises the quality of life of individuals, families, communities and whole societies in a variety of ways. Malaysia acknowledges the problems, implementing policies and health promotion activities in line with the World Health Organization Global Strategy to reduce the harmful use of alcohol by 10% between 2010 and 2025. Sabah, one of two Malaysian states on the island of Borneo, has more than 30 different indigenous ethnic groups. Alcohol production and consumption have traditional and unique roles in the cultural practices of many of these groups, making one common programme difficult to implement. Preliminary research suggests that alcohol is a serious problem in indigenous communities in Sabah. It also shows lack of knowledge on recommended limits for alcohol consumption and understanding of alcohol-related harm. The objective of this action-research is to produce a toolkit that will transfer knowledge and empower communities to adopt safer drinking and reduce alcohol-related harm. It must be attractive, appropriate, easily understood and be able to be tailored to suit different communities. The alcohol tool-kit was developed by a group of academicians using evidence-based information. Qualitative research methods were used to evaluate the initial alcohol tool-kit. A purposive sample of 45 village representatives was selected and divided into 5 groups for focus group discussion. Their feedback was recorded and transcribed verbatim. The alcohol tool-kit was edited accordingly. All participants agreed the alcohol tool-kit was important and can empower communities to reduce alcohol-related harm directly improving their quality of life. The amended alcohol tool-kit will be recommended for health promotion material and evaluated from time to time.